New Approaches for Cryptococcosis Treatment - Cristina de Castro Spadari; Fernanda Wirth; Luciana Biagini Lopes; Kelly Ishida (Microorganisms, 2020)
Cryptococcosis is an important opportunistic infection and a leading cause of meningitis in patients with HIV infection. The antifungal pharmacological treatment is limited to amphotericin B, fluconazole and 5- flucytosine. In addition to the limited pharmacological options, the high toxicity, increased resistance rate and difficulty of the currently available antifungal molecules to cross the blood–brain barrier hamper the treatment. Thus, the search for new alternatives for the treatment of cryptococcal meningitis is extremely necessary. In this review, we describe the therapeutic strategies currently available, discuss new molecules with antifungal potential in different phases of clinical trials and in advanced pre-clinical phase, and examine drug nanocarriers to improve delivery to the central nervous system.